2018
DOI: 10.1002/cctc.201801165
|View full text |Cite
|
Sign up to set email alerts
|

N‐Hydroxyphthalimide (NHPI) Promoted Aerobic Baeyer‐Villiger Oxidation in the Presence of Aldehydes

Abstract: Metal-free aerobic Baeyer-Villiger (BV) oxidation of ketones to lactones or esters in the presence of aldehydes promoted by Nhydroxyphthalimide (NHPI) has been developed. The reaction proceeded under mild conditions with excellent selectivity and high yields. Compared with the methods that use metal complexes as catalysts, this strategy not only showed good environmental advantages, but also increased aldehyde efficiency up to 84 %. Control experiments indicated that NHPI accelerated the oxidation of aldehydes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 56 publications
2
20
0
1
Order By: Relevance
“…In this figure, we learned that both CHOL and CHONE selectivities in the reaction system decreased while ϵ‐CL selectivity increased with the conversion of cyclohexane. These results indicated that ϵ‐CL was easily produced from the in‐situ formed CHONE by Baeyer‐Villiger oxidation in the reaction system …”
Section: Methodsmentioning
confidence: 80%
“…In this figure, we learned that both CHOL and CHONE selectivities in the reaction system decreased while ϵ‐CL selectivity increased with the conversion of cyclohexane. These results indicated that ϵ‐CL was easily produced from the in‐situ formed CHONE by Baeyer‐Villiger oxidation in the reaction system …”
Section: Methodsmentioning
confidence: 80%
“…The autoxidation reactions of alkene 4a (Scheme A,B) appear to proceed through a radical mechanism characteristic of triplet oxygen, as evidenced by the complete inhibition of the reaction in the presence of butylated hydroxytoluene (BHT, Scheme C) . Although the addition of molecular oxygen to alkenes generally involves the excited singlet state of oxygen, autoxidation reactions of alkenes and alkynes involving triplet oxygen have also been observed. Many of these reactions involve geometrically strained compounds, including the autoxidations of aryl-substituted alkylidenecyclopropanes. , …”
mentioning
confidence: 99%
“…Figure 6 In-situ IR spectra of the cyclohexanone oxidation catalyzed by NHPI (inset is the effect of NHPI on the benzaldehyde conversion) [42] (color online).…”
mentioning
confidence: 99%
“…a) 条件: 环己酮, 2.0 mmol; 1,2-二氯乙烷, 20 mL; 温度, 313 K; NHPI, 0.02 mol; 醛, 4.0 mmol. b) 转化率与选择性是基于气相内标法(a)[42] …”
unclassified
See 1 more Smart Citation